Internet connectivity disruption in Finland (Finland) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Finland. Data sourced from IODA.
Network Disruption Incident ID: FI-2026-0004. Severity: critical. Confidence: 65%